2021
DOI: 10.1108/ijse-10-2020-0711
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of financial inclusion on financial well-being of marginalized street vendors: an empirical evidence from India

Abstract: PurposeThe study attempts to explore the determinants of financial inclusion. Subsequently, it examines the effect of financial inclusion on financial well-being of marginalized street vendors in India.Design/methodology/approachThe demand-side analysis of measuring financial inclusion with a sample of 371 marginalized street vendors is adopted. Both exploratory and descriptive research designs are employed in this study. The primary data collection is done by administering the structured interview schedule by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 39 publications
(43 reference statements)
2
29
0
Order By: Relevance
“…Considering the importance of financial inclusion for inclusive development and the gap in adoption of financial services across demographics, several studies have analyzed the factors affecting financial inclusion (Demirg€ uç-Kunt et al, 2013;Del echat et al, 2018;Arnold and Gammage, 2019;Dar and Ahmed, 2020;Kaur and Kapuria, 2020;Oumarou and Celestin, 2021;Nandru et al, 2021). Ghosh and Vinod (2017) have identified different possible factors which hamper financial inclusion and argue that gender disparity badly affects the access to finance among households headed by females in India.…”
Section: Determinants Of Financial Inclusion In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of financial inclusion for inclusive development and the gap in adoption of financial services across demographics, several studies have analyzed the factors affecting financial inclusion (Demirg€ uç-Kunt et al, 2013;Del echat et al, 2018;Arnold and Gammage, 2019;Dar and Ahmed, 2020;Kaur and Kapuria, 2020;Oumarou and Celestin, 2021;Nandru et al, 2021). Ghosh and Vinod (2017) have identified different possible factors which hamper financial inclusion and argue that gender disparity badly affects the access to finance among households headed by females in India.…”
Section: Determinants Of Financial Inclusion In Saudi Arabiamentioning
confidence: 99%
“…, 2013; Deléchat et al. , 2018; Arnold and Gammage, 2019; Dar and Ahmed, 2020; Kaur and Kapuria, 2020; Oumarou and Celestin, 2021; Nandru et al. , 2021).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Besides cultural context, institutional setting influences financial well-being (Brüggen et al 2017; Gonçalves, Ponchio, and Basílio 2021; Nanda and Banerjee 2021). Studies have shown that trust in government increases financial well-being (Barrafrem, Tinghög, and Västfjäll 2021) and that universally accessible formal financial services (high financial inclusion) have a positive effect on financial well-being (Nandru, Chendragiri, and Velayutham 2021). However, these studies have used a single financial well-being score.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Following the responsiveness of global demand for the now cheaper entrepreneurial funds and the resulting upward shift of the GEFD, the long-run market equilibrium ends up at E 3 . Building on [36], who established wellbeing as a core aspect of entrepreneurial fund supply and demand interaction, and on [37], who linked financial inclusion with wellbeing, the above theoretical developments are empirically tested using a Random Utility theoretic formulation of economic agents' behavioral optimization in the global entrepreneurial finance market.…”
Section: Public Sector and Private Sector Financial Injections And The Gefmmentioning
confidence: 99%